2005
DOI: 10.1111/j.1740-8261.2005.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radiographic and Computed Tomography Lymphangiography for Identification of the Canine Thoracic Duct

Abstract: Standard radiographic lymphangiograms and computed tomography (CT) lymphangiograms were performed on 10 female dogs without intrathoracic disease. Positive contrast lymphagiography was performed by injection into a catheterized mesenteric lymphatic vessel, and lateral thoracic radiographs, ventrodorsal thoracic radiographs, and thoracic CTs were obtained. The number of visible ducts was recorded for each image at the midbody of the ninth thoracic vertebra (T9) through the first lumbar vertebra (L1). Data were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 10 publications
1
28
1
Order By: Relevance
“…When performing computed tomography at the established time, we could identify thoracic ducts in all 5 subject dogs. In a previous study, Esteline concluded that computed tomography allows users to identify more thoracic duct branches than is possible with radiographic lymphangiography [4]. Unlike previous studies, our study revealed that there was no significant difference between CT and radiographic image in terms of the number of thoracic ducts in any region.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…When performing computed tomography at the established time, we could identify thoracic ducts in all 5 subject dogs. In a previous study, Esteline concluded that computed tomography allows users to identify more thoracic duct branches than is possible with radiographic lymphangiography [4]. Unlike previous studies, our study revealed that there was no significant difference between CT and radiographic image in terms of the number of thoracic ducts in any region.…”
Section: Discussioncontrasting
confidence: 80%
“…However, patients do not need to be repositioned, images can be manipulated to better observe the target tissue, image contrast is vastly enhanced and small differences in contrast can be detected during computed tomographic scanning [3]. Lymphography using computed tomography for identification of the thoracic duct would be useful for ligation of the thoracic duct [4,12]. Therefore, although the number of thoracic ducts detected by computed tomography and conventional radiography did not significantly differ, it is assumed that computed tomography is the superior modality for delineation of the thoracic duct after popliteal lymphography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R adiography is the most widely used imaging modality for detection of pulmonary nodules in animals. However, computed tomography (CT) has many advantages over radiography for evaluating thoracic disease, 1–4 namely superior contrast resolution and lack of superimposition. CT is more accurate than radiography for detection of lung metastases in dogs and humans 4,5 …”
Section: Introductionmentioning
confidence: 99%
“…Open mesenteric lymphadenography with slow injection of contrast medium directly in a mesenteric lymph node has been described 9 . After mesenteric lymphangiography, a greater number of TD branches were identified by computed tomography (CT) compared with radiography in normal dogs 10 . Regardless of technique used for TD imaging, additional morbidity is associated with the surgical procedure (celiotomy) and with the longer anesthetic time required for the imaging studies 10 …”
mentioning
confidence: 99%